Investigating the effects of retail agglomeration choice behavior on store attractiveness. Issue 2 (July 2016) - Singla, Vikas; Rai, Harpreet
ABSTRACT This study provides an understanding towards linkage between consumers' purchase behavior attributes and store attractiveness. It adds significance to store location decision strategy by undertaking the study in two agglomerations of street shopping area and a shopping mall. Both agglomerations involve clustering of similar stores but have different geographic locations. The study in its first step identifies attributes which influence an individual to purchase from a particular agglomeration. Secondly, the impact of these identified attributes was studied on store attractiveness of both agglomerations. Store attractiveness was measured in terms of time being spent and intention to revisit an agglomeration. The results suggested that in addition to depth and variety of stores, merchandise characteristics such as price of merchandise and accessibility influence an individuals' store selection decision. It was found that the degree of influence varies with type of agglomeration.